2017
DOI: 10.5455/jice.20170819054925
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of magnesium lactate gluconate and Garcinia cambogia fruit extract in experimentally induced renal calculi in rats

Abstract: Aim: Antiurolithiatic activity of magnesium lactate gluconate (MLG) and aqueous extract of Garcinia cambogia (GC) fruit was studied. Materials and Methods: The study was performed during December 2016 to April 2017. Urolithiasis was induced in male Wistar rats by administration of 0.75% v/v ethylene glycol for 21 days. From 8 th day onward, intervention with MLG (200 and 400 mg/kg b.w.) and GC (100 and 200 mg/kg b.w.) was started. At the end of the treatment period, biochemical parameters affecting renal stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Experimental animal studies demonstrated the effect of HCA on the inhibition of the crystallization of calcium oxalate, and in addition, its renal elimination. Therefore, HCA has a double effect: a prophylactic effect in the first case and a therapeutic effect in the second one [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental animal studies demonstrated the effect of HCA on the inhibition of the crystallization of calcium oxalate, and in addition, its renal elimination. Therefore, HCA has a double effect: a prophylactic effect in the first case and a therapeutic effect in the second one [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%